Characterization of the complete chloroplast genome sequence of Actinidia kolomikta - Dongping Qiu; Ping Tang; Xiaohong Yao (Mitochondrial DNA. Part B. Resources, 2021)
The whole complete chloroplast (cp) genome sequence of Actinidia kolomikta (formerly A. maloide) was sequenced and assembled from Illumina paired-end sequencing. The cp genome of A. arguta was 157,425 bp long, containing a large single copy region (LSC) of 88,498 bp and a small single copy region (SSC) of 20,475 bp and a pair of inverted repeat regions (IR) of 242,266 bp. It contained 113 different genes, including 79 protein-coding genes, 30 tRNA genes, 4 ribosomal RNA genes. Phylogenetic analysis using concatenated alignments of whole cp genome sequences revealed that A. kolomikta was the sister group to all other groups of Actinidia